Effectiveness of Emotion-Focused Couple Therapy and Integrative Systemic Couple Therapy on Enhancing Psychological Well-Being in Couples with Attachment Injury - Hoseinian, Simin Dokht (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aims to assess the effectiveness of Emotion-Focused Therapy (EFT) and Integrative Systemic Therapy in enhancing psychological well-being in couples with attachment wounds. Methods and Materials: A semi-experimental design with a pre-test and post-test approach was used in this study. Forty couples, selected from counseling centers in Tehran and Alborz, were randomly assigned to either an experimental group or a control group. The experimental group received EFT and Integrative Systemic Therapy, while the control group did not receive any treatment. Psychological well-being was assessed using the Ryff Psychological Well-Being Scale, which measures six dimensions: self-acceptance, personal growth, purpose in life, environmental mastery, autonomy, and positive relations with others. The interventions lasted for 8 sessions, and data were analyzed using ANCOVA to determine the effects of the treatments. Findings: The results showed that both EFT and Integrative Systemic Therapy led to significant improvements in psychological well-being compared to the control group. ANCOVA analyses revealed large effect sizes for both treatments, with EFT showing slightly stronger effects. The pre-test scores were statistically controlled, confirming that the post-test differences were due to the interventions. Both therapeutic approaches were highly effective in enhancing the couples’ psychological well-being. Conclusion: Both EFT and Integrative Systemic Therapy significantly improved psychological well-being in couples with attachment wounds. These results suggest that both therapies are effective interventions for enhancing relationship dynamics and emotional health in couples experiencing attachment-related challenges.